Effects of selected factors on rheological and textural properties of probiotic yoghurt - Jovana Glušac; Vladimir Vukić; Spasenija Milanović; Milka Stijepić; Katarina Kanurić; Dragica Đurđević-Milošević; Marjan Ranogajec (Mljekarstvo)
The aim of this work was to study the influence of inulin (1 %), combination of inulin (1 %) and acacia honey (4 %), heat treatment of milk, and storage time on the rheological and textural properties of probiotic yoghurt. Rheological properties were assessed trough viscosity, syneresis and texture (firmness, consistency, cohesiveness and index of viscosity). Yoghurt was prepared from milk (1,5 % fat) with added inulin (1%) before heat treatment at 85 °C for 20 min or 95 °C for 10 min. After cooling to 55 °C honey (4 %) was added. Samples were inoculated using probiotic starter culture (70 % w/w Streptococcus thermophilus, 10 % w/w Lactobacillus bulgaricus, 10 % w/w Lactobacillus acidophilus, 10 % w/w Bifidobacterium ssp.). Yoghurt samples were held on +5 °C during 21 days. Measurements of pH value, lactic acid, viscosity, syneresis, and textural properties were done after 1, 7, 14 and 21 days of storage. The results of this study show that honey addition significantly decreased fermentation time compared to fermentation time of control samples or samples containing inulin. Furthermore, addition of honey and inulin to milk caused significant lower syneresis (p<0,05) during storage time, while there was no significant influence on viscosity and texture of final product. The applied heat treatment of milk had no significant influence on rheological properties of probiotic yoghurt.